2009
DOI: 10.1115/1.3176960
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Break of Symmetry in Unconfined Laminar Annular Jets

Abstract: Numerical investigations show that the spontaneous break of symmetry in annular incompressible jets occurs in the laminar flow regime and is controlled by both the Reynolds number and the blockage ratio. In the blockage ratio range between 0.50 and 0.89 the transition critical Reynolds number decreases with increasing blockage ratio, according to a defined formula. Transition to asymmetry happens in the steady regime, before the transition to the unsteady flow. Asymmetry is characterized by a preferential flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
3
11
0
Order By: Relevance
“…The mechanism of disturbances proposed by Del Taglia et al 11 is unable to explain the low frequency motions of the stagnation point since the frequencies associated with their convective timescales are much higher. Therefore, we suggest a model which involves feedback from the stagnation point back to the inner shear layer.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…The mechanism of disturbances proposed by Del Taglia et al 11 is unable to explain the low frequency motions of the stagnation point since the frequencies associated with their convective timescales are much higher. Therefore, we suggest a model which involves feedback from the stagnation point back to the inner shear layer.…”
Section: Resultsmentioning
confidence: 83%
“…This symmetry breaking of annular jets is also reported in literature by Del Taglia et al 10 In their numerical study, symmetry breaking occurred even for symmetric boundary conditions. A simple mechanism for the transition to asymmetry is proposed in another paper by Del Taglia et al 11 They stated that perturbations in the inner shear layer near the nozzle exit are convected towards the stagnation point and cause there a shift in location. In order to study the large scale motions of the wake, a POD decomposition of the wake is performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape of this zone can be controlled by varying Reynolds number and nozzle dimensions, mainly the blockage ratio of the bluff body. The studies of del Taglia et al [11] and Vanierschot et al [12] showed that in non-swirling conditions, the CRZ symmetry breaks up above a critical Reynolds number. Even though the turbulent behaviour of the CRZ can be characterized according to flow velocity, the position of the stagnation point solely depends on the nozzle geometry in isothermal and non-swirling conditions.…”
Section: Introductionmentioning
confidence: 98%
“…Although the flow has both a symmetric geometry and symmetric boundary conditions, the investigations on turbulent annular jets have shown that spontaneous break of symmetry of the time-averaged flow field could appear [9][10][11][12][13][14] . This type of asymmetry is observed in laminar annular jets as well, if the Reynolds number is above a certain threshold value, which is around 150 for the geometry used in this study [15] .…”
Section: Introductionmentioning
confidence: 99%